The EQ leader : instilling passion, creating shared goals, and building meaningful organizations through emotional intelligence - Stein, Steven (Steven J.) (John Wiley & Sons, Inc., 2017)
A roadmap to success for tomorrow's leaders, this step-by-step guide provides an evidence-based model for exceptional leadership, and a four-pillar roadmap for real-world practice. --